ANALISIS PERBANDINGAN KINERJA KEUANGAN PERBANKAN SYARIAH DENGAN PERBANKAN KONVENSIONAL DI BURSA EFEK INDONESIA - NILA PRATIWI; PUTRI FANNY ALITA (Maqdis: Jurnal Kajian Ekonomi Islam, 2018)
The purpose of this study is to analyze the financial performance of sharia banking with conventional banking. The type of research is quantitative research. The type of data used is secondary data, ie annual report period 2011-2016. The research variables are financial ratios which consist of Capital Adequacy Ratio, Non Performing Loan, Return on Asset, Operational Revenue Operating Expense, and Loan to Deposit Ratio. The analysis technique used is Paired sample t-test. The results of this study show: 1) There are significant differences in financial performance between sharia banking and conventional banking, 2) In terms of profitability (ROA) and liquidity (LDR) financial performance of sharia banks is better than conventional banking, 3) There are several ratios sharia banking is lower than conventional banking, namely the capital ratio (CAR), asset quality (NPL) ratio, and efficiency ratio (BOPO).